Automate Snort Rule For Xss Detection With Honeypot - Syaifuddin Syaifuddin; Diah Risqiwati; Hanugra Sidharta (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
In modern era, data become precious and important, if there is occurrence data leakage will cause high damage to business, data loss will impact on loosing profit. To avoiding that, organization need equip with updated security tools for protect data and network from malicious software and hacker attack. As computer network growing day by day, security become important role to preventing from attack from outside and inside network. Unfortunetely, new vulnerability finds almost every day, resulting increment number of intrusion and attack. Meanwhile each intrusion and attack have different pattern and behavior, continuous development on intrusion detection is mandatory. In 2011, most attack associate with XSS, 12.58% attack is XSS followed by Denial of Service (DOS) 8.06%.